LNA real-time PCR probe quantification of hepatitis B virus DNA - WANG, QING (D.A. Spandidos, 2012)
In the present study, we standardized a TaqMan locked nucleic acid (LNA) real-time polymerase chain reaction (PCR) probe for the accurate quantification and detection of hepatitis B virus (HBV) DNA in serum (plasma), and evaluated its methodology. LNA probe technology had a much better detection performance in HBV DNA than the common TaqMan probe. The assay based on the LNA probe had a wider linear detection range, higher sensitivity, stability and amplification efficiency, and a lower concentration of probes than the TaqMan probe. Among the 15 cases with chronic hepatitis B surface antigen (HBsAg) (+) alone, only 4 cases that were detected by TaqMan real-time PCR were negative; however, the same samples were positive by LNA real-time PCR (p<0.05). A positive correlation between viral load measurements for the 35 samples with HBV-positive DNA was detected in both LNA and TaqMan real-time PCR.